Tissue Factor Activity Is Upregulated in Human Endothelial Cells Exposed to Oscillatory Shear Stress - Mazzolai, Lucia; Silacci, Paolo; Bouzourene, Karima; Daniel, François; Brunner, Hans; Hayoz, Daniel (Thrombosis and Haemostasis, 2002)
Hemodynamic forces play a critical role in the pathogenesis of atherosclerosis as evidenced by the focal nature of the disease. Oscillatory shear stress characterizes the hemodynamic environment of plaque-prone areas as opposed to unidirectional shear stress typical of plaque-free areas. These particular flow conditions modulate atherosclerosis-related genes. Tissue factor (TF) initiates blood coagulation, contributes to vascular remodeling, and is therefore a potential contributor in the development/progression of atherosclerosis. We investigated the effect of oscillatory and unidirectional flows on TF using an in vitro perfusion system. Human endothelial cells exposed for 24 h to oscillatory shear stress, significantly increased TF mRNA, and TF protein expression (1.5-and 1.75-fold, respectively, p <0.01), and surface TF activity (twofolds-increase). Expression of TF inhibitor (TFPI), mRNA and protein, remained unchanged as compared to static conditions. Conversely, cells exposed to unidirectional shear, showed a decrease in TF activity with a significant increase in TFPI mRNA and protein expression (1.5-and 1.8-fold, respectively, p <0.01). These results show for the first time that pulsatile oscillatory shear stress induces a procoagulant phenotype of endothelial cells which may favor formation/progression of atherothrombotic lesions.
Keywords: Tissue factor; tissue factor pathway inhibitor; shear stress; oscillatory flow; atherosclerosis